Laser Doppler Flowmetry as a method of analysis for the evaluation of chemo - induced oral mucositis: A pilot study. - Emanoele Paixão da Silva Silva; Raquel D'Aquino Garcia Caminha; Marcelo Junior Zanda; Paulo Sérgio da Silva Santos (Universidad de Concepción., 2020)
Background: Oral mucositis (OM) is an inflammation of the oral mucosa due to cancer therapy that compromises the patient's quality of life. Laser Doppler flowmetry (LDF) is a non-invasive method to monitor microvascular blood flow (BF) in real-time. Purpose: Develop a method to evaluate BF in the genian region cheek in patients undergoing chemotherapy by LDF and compare the degrees of OM and pain with evaluation of BF. Material and methods: Evaluation of OM was performed using the World Health Organization (WHO) and Oral Mucositis Assessment Scale (OMAS) scales and the visual analog scale for pain evaluation. For flowmetry analysis, a laser Doppler flowmeter (moorVMSTM™, 780 nm wavelength and VP3 probe), fixed by an acrylic resin support was used; VP3 probe was positioned on the genian region and the patient's head was stabilized with a neck pillow for an accurate measurement. The Wilcoxon test was used to compare the flowmetry results at the studied times. The Pearson correlation coefficient was used to evaluate relationships between BF and the WHO, OMAS and visual analog scales. Results: Eleven patients of both sexes, aged between 30 and 78 years, with OM were included. An increase in cutaneous BF was observed at the initial times of OM, with progressive reduction during the chemotherapy cycle. There was a statistical difference (p<0.05) between time point T0 (first consultation) and time point T6 (last consultation). Conclusion: The method developed in this pilot study is effective, reliable, and reproducible, and allows the evaluation of BF dynamics in the genian region using LDF of patients undergoing chemotherapy at risk of developing OM.